PENDIDIKAN DALAM PERSPEKTIF AL-QUR’AN - Eka Eramahi (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2017)
According to Qoran, education is aimed at helping students do their functions to worship Allah swt. All potencies that students have, namely, intelectual potency, soul, and body must be integratically built in balance and harmony which are reflected in real human being. This must be implimented in teaching method and material and other related things. This in turn will result in a perfect education system.